Implementation of the Independent Curriculum in Zero Waste Application Through the Based Learning Method - Mahsun, Muhammad; Amelia, Dwi Wilda; Khulailah, Sofwah (Proceedings of Sunan Ampel International Conference of Political and Social Sciences, 2024)
The implementation of the Independent Curriculum is one of the important initiatives in improving the quality of education in Indonesia, especially in equipping students with 21st century skills. One of the main challenges faced is how to apply sustainability principles, such as the concept of zero waste into relevant and contextual learning. This article aims to analyze how the Independent Curriculum can be applied in the application of the concept of zero waste through based learning methods, such as Project-Based Learning (PjBL) and Problem-Based Learning (PBL). The method used in this study is a case study in a school that has implemented the Independent Curriculum with a focus on the zero waste program. Data was collected through direct observation, in-depth interviews with teachers and students, and analysis of curriculum documents and student project results. The analysis was carried out to assess the effectiveness of the application of the based learning method in facilitating students' understanding of the principle of zero waste and the relationship between learning materials and real life. The results of the study show that the implementation of the Independent Curriculum through the based learning method is effective in increasing students' awareness of the importance of zero waste and encouraging them to be actively involved in real projects that have an impact on the environment. In addition, students show significant improvements in critical thinking, collaboration, and problem-solving skills. The conclusion of this study is that the Independent Curriculum, when combined with the based learning method, has great potential to encourage education that is not only academically relevant but also has a positive impact on the environment and society